Pengaruh Economic Performance, Leverage, Ukuran Perusahaan, dan Dewan Komisaris Independen terhadap Pengungkapan Corporate Social Responsibility - Nabila Putri Dwi Septiani; Triyono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Corporate Social Responsibility (CSR) is a company's commitment to behave ethically and contribute to economic development, by improving the quality of life of employees, their families, as well as local communities and society at large. CSR aims to create a balance between business interests and concern for the surrounding social environment, so as to build good relationships with the public and stakeholders. This study aims to analyze the effect of Economic Performance, Leverage, Company Size, and Independent Board of Commissioners on Corporate Social Responsibility Disclosure in non-cyclical consumer sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Sampling was carried out using purposive sampling technique. The results of this study indicate that company size has an effect on corporate social responsibility disclosure. Meanwhile, economic performance, leverage, and the independent board of commissioners have no effect on corporate social responsibility disclosure.